Strategi Promosi Kerajinan Besi Di Desa Limbang Jaya Kabupaten Ogan Ilir Sumatera Selatan - M.Havest Al Fayed (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Indonesia is renowned for its cultural diversity, with each region preserving significant historical and artistic values. Limbang Jaya Village in Ogan Ilir Regency, South Sumatra, is one of the regions that maintains a unique tradition of iron craftsmanship. Known locally as Pandai Besi (blacksmiths), these craftsmen create ironworks that not only serve practical purposes in daily life but also reflect cultural and artistic heritage passed down through generations. However, despite its cultural significance, this traditional craft remains relatively unknown to wider audiences, particularly outside its local community. This study focuses on the design of visual communication strategies to promote the iron craftsmanship of Limbang Jaya Village. The design process involved field observations, direct interviews with local blacksmiths, and a review of literature on branding strategies for traditional crafts. The aim is to develop promotional media that effectively introduces the craft, enhances public appreciation of its artistic and cultural values, and expands its market reach. The expected outcomes of this design project include greater exposure of Limbang Jaya’s iron craftsmanship, increased recognition of its cultural value, and contributions to local economic development, ultimately improving the welfare of the blacksmiths in the community